Pengaruh Self Efficacy dan Self Esteem Terhadap Prestasi Akademik Mahasiswa Fakultas Ekonomika dan Bisnis Universitas Stikubank Semarang - Fadhil Subandrio; Suhana (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research was conducted at Stikubank University Semarang at the Faculty of Economics and Business. This research aims to analyze the influence of self-efficacy and self-esteem on student academic achievement. This research has a population of 1,160 students registered at the faculty of economics and business. The sampling technique uses a non-probability sampling method with a purposive sampling technique with criteria for students from semester 4 to semester 8. The number of samples in this research is 100 respondents. The results of this research shows that self-efficacy has a positive and significant effect on student academic achievement, self-esteem has a positive and significant effect on student academic achievement.